2019
DOI: 10.1080/02656736.2019.1685686
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the abscopal effect of radiation and immune checkpoint inhibitor therapies with magnetic nanoparticle hyperthermia in a model of metastatic breast cancer

Abstract: Purpose: Enhancing immune responses in triple negative breast cancers (TNBCs) remains a challenge. Our study aimed to determine whether magnetic iron oxide nanoparticle (MION) hyperthermia (HT) can enhance abscopal effects with radiotherapy (RT) and immune checkpoint inhibitors (IT) in a metastatic TNBC model. Methods: One week after implanting 4T1-luc cells into the mammary glands of BALB/c mice, tumors were treated with RT (3 Â 8 Gy)±local HT, mild (HT M , 43 C/20 min) or partially ablative (HT Abl , 45 C/ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 76 publications
(172 reference statements)
1
36
0
Order By: Relevance
“…A case report also found that hyperthermia and ipilimumab combined with IL-2 achieved complete clinical remission of stage IV triple-negative breast cancer with lung metastasis (127). Despite the favorable results, a preclinical study combining magnetic iron oxide nanoparticle hyperthermia and anti-PD-1 and anti-CTLA-4 with a 4T1-luc cell mouse model also showed decreased tumor volume but increased metastatic dissemination and no improvement in overall survival (128). In fact, a study has shown that tumors quickly overcame immune responses by inhibiting the function of CD8 and CD4 T cells, driving a shift to a higher Treg/Teff ratio and upregulating PD-L1/PD-1 expression, which result suggested that tumor microenvironment after hyperthermia is variable and is favorable for anti-PD-1/PD-L1mAb treatment for only a narrow time window (105).…”
Section: Preclinical Data Combining Hyperthermia and Icismentioning
confidence: 99%
“…A case report also found that hyperthermia and ipilimumab combined with IL-2 achieved complete clinical remission of stage IV triple-negative breast cancer with lung metastasis (127). Despite the favorable results, a preclinical study combining magnetic iron oxide nanoparticle hyperthermia and anti-PD-1 and anti-CTLA-4 with a 4T1-luc cell mouse model also showed decreased tumor volume but increased metastatic dissemination and no improvement in overall survival (128). In fact, a study has shown that tumors quickly overcame immune responses by inhibiting the function of CD8 and CD4 T cells, driving a shift to a higher Treg/Teff ratio and upregulating PD-L1/PD-1 expression, which result suggested that tumor microenvironment after hyperthermia is variable and is favorable for anti-PD-1/PD-L1mAb treatment for only a narrow time window (105).…”
Section: Preclinical Data Combining Hyperthermia and Icismentioning
confidence: 99%
“…A breakthrough in heat-triggered tumor targeted drug delivery is one trend that would further strengthen popularity of the combination with chemotherapy [70,268,[274][275][276][277]. Finally, the recent trend to combine thermal therapies with immunotherapies has demonstrated significant potential to address recurrence and metastasis in preclinical and clinical pilot studies [425][426][427][428]. When this is supported by further clinical evidence, a further growing interest in hyperthermic applications can be expected.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…An enhanced populations of T-cells following the combinatorial therapies presumably due to greate tumor damage/necrosis relative to monotherapy in tumors were noted. Although promising, the abscopal effects using this approach was modest [144]. These studies (Table 2) suggest that optimizing the MNP hyperthermia duration, frequency, and precise control of thermal energy deposition is needed prior to its application as an ISV.…”
Section: Magnetic Np-isvmentioning
confidence: 99%